Product Quality, Promotion And Price Perception Of Purchasing Decisions (Study On Consumers Of Kopi Janji Jiwa Tembalang Semarang City) - widyakto, adhi; puspitasari, diana; suryawardana, edy (Faculty of Economics and Business | Universitas Diponegoro, 2021)
The consequences of product quality, promotion, and price assumption to the purchase decision in Coffee Kopi Janji Jiwatembalang Semarang. Respondents wore non-random sampling illustration methods. This illustration is wearing Purposive Sampling method, there are also criteria used are consumers or customers of the lowest age of 15 years, minimun once tasted coffee Kopi Janji Jiwa Semarang and the last had arrived at Kopi Janji Jiwa Tembalang Semarang. Methods of collecting information by wearing questionnaires and have been tested for validity and reliability. In testing product quality variables, the promotional decameter price assumption to the researcher's purchase provisions put on multiple linear regression analysis. There are also results showing if the quality of the product, promotion and price assumptions have a positive and significant influence.